2010
DOI: 10.2353/ajpath.2010.091088
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Deficiency Dampens Toll-Like Receptor 4 Signaling through eNOS Activation

Abstract: Caveolin-1 (Cav1), the scaffolding protein of caveolae, has been shown to play an important role in host defense and inflammation. However , the underlying molecular basis for these actions remains elusive. Here , using double mutant mice with genetic deletions of Cav1 and NOS3 , we show that chronic endothelial nitric oxide synthase (eNOS) activation secondary to loss of Cav1 serves a crucial immunomodulatory function through tyrosine nitration-mediated impairment of interleukin-1 receptor associated kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
76
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 44 publications
(52 reference statements)
13
76
1
Order By: Relevance
“…26,43 Indeed, reduced angiogenesis in the absence of eNOS is confirmed in our experiments from the in vitro, ex vivo and in vivo angiogenic phenotype of Cav ϩ/ϩ eNOS Ϫ/Ϫ mice, and substantiated by the reduced angiogenesis in wild-type mice treated with L-NAME. In agreement with our results, excess NO production has been shown to mediate other aspects of the phenotype of caveolin-1 knock-out mice, namely pulmonary hypertension 44,45 even though NO per se is a potent vasodilator, reduction of innate immunity 46 even though NO has direct and indirect antimicrobial activities, and cardiomyopathy. 47 One mechanism for these consequences of increased eNOS activity in caveolin-1-null mice has been proposed to be the formation of peroxinitrite when NO is combined to superoxide, and the subsequent deleterious nitration reactions affecting functional proteins such as protein kinase G 41 or interleukin-1 receptor-associated kinase.…”
Section: Discussionsupporting
confidence: 80%
“…26,43 Indeed, reduced angiogenesis in the absence of eNOS is confirmed in our experiments from the in vitro, ex vivo and in vivo angiogenic phenotype of Cav ϩ/ϩ eNOS Ϫ/Ϫ mice, and substantiated by the reduced angiogenesis in wild-type mice treated with L-NAME. In agreement with our results, excess NO production has been shown to mediate other aspects of the phenotype of caveolin-1 knock-out mice, namely pulmonary hypertension 44,45 even though NO per se is a potent vasodilator, reduction of innate immunity 46 even though NO has direct and indirect antimicrobial activities, and cardiomyopathy. 47 One mechanism for these consequences of increased eNOS activity in caveolin-1-null mice has been proposed to be the formation of peroxinitrite when NO is combined to superoxide, and the subsequent deleterious nitration reactions affecting functional proteins such as protein kinase G 41 or interleukin-1 receptor-associated kinase.…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that cav-1 participates in the rapid signaling elicited by the hormone (54). Cav-1, the scaffolding protein of caveolae, has also been shown to play an important role in host defense and inflammation (55). Increased cav-1 in the heart noted in our results suggests that the tissues were greatly damaged after having undergoing CPZ-induced toxicity.…”
Section: Discussionsupporting
confidence: 57%
“…In these disease models, the functions of Cav-1 in disease pathogenesis appear to be mediated, at least in part, by autophagy. In lipopolysaccharide (LPS)-induced lung inflammation and sepsis models, deletion of Cav-1 resulted in decreased production of inflammatory mediators and animal mortality (10,27), but whether this function of Cav-1 is due to autophagy remains unclear, although recently autophagy has been shown to suppress LPS-induced inflammation and LC3B-deficient mice were more susceptible to LPS-induced mortality (31).…”
Section: Discussionmentioning
confidence: 99%